(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Thanks to the archaeological excavations started more than thirty years ago by the University of Milan in the Roman vicus of Calvatone-Bedriacum a sector of the ancient town characterized by rich residential quarters, production and public areas has explored, returning the image of a lively commercial emporium. Among the thousands of fragmentary finds from the town, and coming from all the provinces of the Empire, a lamp is noted because of its particular decoration, the representation on the disk of one of the twelve labors of Hercules. The iconographic analysis of the subject allows us to recognize in the figurative scheme the fight of the hero against the serpent Ladon for the conquest of the gold apples in the garden of the Hesperides, rather than the fight against the Hydra of Lerna.